2020
DOI: 10.3390/nu12020501
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Exercise-Induced Muscle Damage, Inflammation, and Oxidative Markers by Curcumin Supplementation in a Physically Active Population: A Systematic Review

Abstract: Physical activity, particularly high-intensity eccentric muscle contractions, produces exercise-induced muscle damage (EIMD). The breakdown of muscle fibers and the consequent inflammatory responses derived from EIMD affect exercise performance. Curcumin, a natural polyphenol extracted from turmeric, has been shown to have mainly antioxidant and also anti-inflammatory properties. This effect of curcumin could improve EIMD and exercise performance. The main objective of this systematic review was to critically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
106
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 121 publications
(136 citation statements)
references
References 47 publications
(201 reference statements)
3
106
1
2
Order By: Relevance
“…In addition, because Ca 2+ is also the vital messenger for the TCR-induced NF-κB signaling pathway, it provides another mechanism by which curcumin suppresses the NF-κB activation [76]. A systematic review revealed that curcumin can make its anti-inflammatory effect by modifying several proinflammatory cytokines (e.g., TNF-α, IL-6, and IL-8) in a physically active cohort [77]. e mentioned action was also observed in an in vitro model of intestinal inflammation.…”
Section: Antioxidant and Anti-inflammatory Activitymentioning
confidence: 99%
“…In addition, because Ca 2+ is also the vital messenger for the TCR-induced NF-κB signaling pathway, it provides another mechanism by which curcumin suppresses the NF-κB activation [76]. A systematic review revealed that curcumin can make its anti-inflammatory effect by modifying several proinflammatory cytokines (e.g., TNF-α, IL-6, and IL-8) in a physically active cohort [77]. e mentioned action was also observed in an in vitro model of intestinal inflammation.…”
Section: Antioxidant and Anti-inflammatory Activitymentioning
confidence: 99%
“…This result may be explained because of the high bioavailability of organic and inorganic Se supplements. The bio bioavailability is substantially higher the bioavailability of other antioxidant supplements such as curcumin, which is administered together with piperine as a bioavailability enhancer [7]. The Se supplementation intake of 180 or 240 µg/day (selenomethionine) and 200 µg/day (sodium selenite) may safely be used as an "enhancer" of the antioxidant defense systems.…”
Section: Selenium Supplementationmentioning
confidence: 99%
“…During physical exercise, oxygen consumption increases between 10 and 15 times above the resting values and may trigger an elevated production of reactive oxygen species (ROS) [6]. Under physiological conditions, antioxidant systems (enzymatic and non-enzymatic systems) neutralizes the harmful effects of ROS [7]. The selenoprotein family is encoded by 25 genes [8], and two of these genes encode the enzyme glutathione peroxidase (GPx) and the enzyme glutathione reductase (GR).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations